Updated quantitative risk assessment (QRA) of the BSE risk posed by processed animal protein (PAP). (17th July 2018) - ,; Ricci, Antonia; Allende, Ana; Bolton, Declan; Chemaly, Marianne; Davies, Robert; Fernández Escámez, Pablo Salvador; Gironés, Rosina; Herman, Lieve; Koutsoumanis, Kostas; Lindqvist, Roland; Nørrung, Birgit; et al.
Abstract: EFSA was requested: to assess the impact of a proposed quantitative real‐time polymerase chain reaction (qPCR) 'technical zero' on the limit of detection of official controls for constituents of ruminant origin in feed, to review and update the 2011 QRA, and to estimate the cattle bovine spongiform encephalopathy (BSE) risk posed by the contamination of feed with BSE‐infected bovine‐derived processed animal protein (PAP), should pig PAP be re‐authorised in poultry feed and vice versa, using both light microscopy and ruminant qPCR methods, and action limits of 100, 150, 200, 250 and 300 DNA copies. The current qPCR cannot discriminate between legitimately added bovine material and unauthorised contamination, or determine if any detected ruminant material is associated with BSE infectivity. The sensitivity of the surveillance for the detection of material of ruminant origin in feed is currently limited due to the heterogeneous distribution of the material, practicalities of sampling and test performance. A 'technical zero' will further reduce it. The updated model estimated a total BSE infectivity four times lower than that estimated in 2011, with less than one new case of BSE expected to arise each year. In the hypothetical scenario of a whole carcass of an infected cow entering the feed chain without any removal of specified risk material (SRM) or reduction of BSE infectivity via rendering, up to four new cases of BSE could be expected at the upper 95th percentile. A second model estimated that at least half of the feed containing material of ruminant origin will not be detected or removed from the feed chain, if an interpretation cut‐off point of 100 DNA copies or more is applied. If the probability of a contaminated feed sample increased to 5%, with an interpretation cut‐off point of 300 DNA copies, there would be a fourfold increase in the proportion of all produced feed that is contaminated but not detected.